Role of Spirometry in Early Diagnosis of COPD among Smokers (TAJ: Journal of Teachers Association, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a major cause of chronic morbidity and mortality throughout the world. Many people suffer from this disease for many years and die prematurely from it or its complications. COPD is a preventable and treatable pulmonary disease. In early stage, diagnosis of COPD is difficult because sign & symptoms are minimum. Only history of mild dyspnea, cough and/or sputum production or prolong smoking, exposure to occupational dusts or biomass fuels are present without any sign. Spirometry is the tool to diagnose COPD. If we can diagnose COPD in early stage then it is treatable and can prevent progression of the disease. Spirometry is a simple tool to diagnose COPD at any health care level. So this study was done to diagnose COPD in early stage among smokers. This study was carried out in Department of Medicine (Indoor & outdoor) of Rajshahi Medical College Hospital from March, 2010 to February, 2011. 255 smoker having exposure to >10 pack year smoking fulfilling inclusion and exclusion criteria were included and 300 apparently healthy non-smoker also were included as control. Both male & female were included with age of the study population were from 30 years to 70 years. All of that study population was free from diseases which alter spirometric measurement. This exclusion was done by history, thorough clinical examination and relevant investigations. Among smokers, clinically 9(4.03%) were diagnosed to have COPD only and the spirometry also diagnosed these 9 smokers and other 32 smokers more to have COPD and thus diagnose 41(18.38%) smokers to have COPD. The difference between clinical and spirometric diagnosis of COPD is statistically highly significant. The test done was Fisher’s Exact Test, where p value is 0.000. So, spirometry is considered as a simple valuable instrument to diagnose COPD in early stage among smokers.TAJ 2019; 32(1): 33-38